Fortifying Future IoT Security: A Comprehensive Review on Lightweight Post-Quantum Cryptography - Mahdi, Liyth H.; A. Abdullah, Alharith (Engineering, Technology & Applied Science Research, 2025)
This paper presents lightweight Post-Quantum Cryptography (PQC), identifying its importance for a shift from traditional cryptographic schemes, vulnerable to quantum threats, to efficient PQC algorithms. Lattice-based cryptography stands out owing to its small key sizes and computational efficiency, with CRYSTALS-Kyber and NTRU algorithms being substantial representatives for Internet of Things (IoT) applications. However, PQC implementation in IoT environments has various obstacles to overcome. Minimizing energy consumption, scalability, and hardware limitations remain key challenges for PQC smooth integration into these resource-constrained networks. The present review analyzes the state-of-the-art PQC, makes security and performance comparisons among leading algorithms, and evaluates optimization techniques aimed at reducing resource overheads. Algorithmic refinement, hardware acceleration, and hybrid cryptography are also discussed as methods for mitigating these challenges. The results indicate that continuous research and development efforts should be made to improve the PQC technologies, and thus achieve their practical deployment in IoT systems. Quantum threats in IoT will be, hence, prevented with the employment of secure and scalable IoT ecosystems in a post-quantum world.